FAT10 is a proteasomal degradation signal that is itself regulated by ubiquitination - Buchsbaum, Samuel (The American Society for Cell Biology, 2012)
FAT10 is a ubiquitin-like protein modifier that is induced in vertebrates following certain inflammatory stimuli. Its functions and the repertoire of its target substrates have remained elusive. In contrast to ubiquitin, its cellular abundance is tightly controlled by both transcriptional and posttranslational regulation, and it was reported to be rapidly degraded by the proteasome. Here we provide data to indicate that the degradation of FAT10 requires ubiquitination: degradation was inhibited in cells expressing a ubiquitin mutant that cannot be polymerized and in a mutant cell harboring a thermolabile ubiquitin-activating enzyme, E1. Of importance, FAT10 can serve as a degradation signal for otherwise stable proteins, and in this case, too, the targeting to the proteasome requires ubiquitination. Degradation of FAT10 is accelerated after induction of apoptosis, suggesting that it plays a role in prosurvival pathways.